Coating composition for coating the surface of a secondary battery electrode active material and secondary battery electrode material comprising the same
Patent Information
- Application Number
- CN202580020221.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2025-06-23
- Filing Date
- 2025-06-24
- Publication Date
- 2026-10-16
AI Technical Summary
然而,根据所使用的沥青不同,存在二次电池的性能不一致的问题
在根据本发明的用于包覆二次电池电极活性材料的表面的包覆组合物和包括该包覆组合物的二次电池电极材料中,通过在电极活性材料的表面上形成包括软化点为200℃至270℃的石油沥青的包覆层,确保了包覆层的晶体结构和/或包覆均匀性,从而可以显著改善应用该电极材料的二次电池的性能,特别是寿命特性。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to a coating composition for coating the surface of an active material for a secondary battery electrode, and a secondary battery electrode material comprising the coating composition, the coating composition comprising petroleum bitumen with a softening point of 200°C to 270°C. Background Technology
[0002] With the rapid increase in the use of fossil fuels, the demand for alternative or clean energy sources is growing, and as part of this, the field of power generation and energy storage using electrochemical reactions is one of the most active areas of research.
[0003] Currently, secondary batteries are a representative example of electrochemical devices utilizing this electrochemical energy, and their application scope is gradually expanding. In recent years, with the technological development and increasing demand for portable devices such as portable computers, mobile phones, and cameras, the demand for secondary batteries as an energy source has also increased dramatically. Among these secondary batteries, lithium secondary batteries with high energy density, i.e., high capacity, have been extensively studied, commercialized, and widely used.
[0004] Generally, a secondary battery consists of a positive electrode, a negative electrode, an electrolyte, and a separator. The positive electrode material, constituting the positive electrode of a lithium-ion secondary battery, uses metal oxides such as LiCoO2, Li(NiCoMn)O2, Li(NiCoAl)O2, LiFePO4, LiMnO2, LiMn2O4, or LiCrO2. The negative electrode material uses carbon-based materials such as lithium metal, graphite, or activated carbon, or materials such as silicon oxide (SiOx). Early negative electrode materials primarily used lithium metal; however, with charge-discharge cycles, lithium atoms grow on the surface of the lithium metal, damaging the separator and causing battery failure. Therefore, carbon-based materials have become the primary choice in recent years. However, carbon-based materials have the disadvantage of low capacity, with a theoretical capacity of only about 400 mAh / g. Therefore, various studies are underway to replace such carbon-based materials with high-capacity materials as negative electrode materials, such as silicon (Si), which has a high theoretical capacity (4,200 mAh / g).
[0005] Meanwhile, when using anode materials such as silicon, a technique of coating the surface of the anode material with asphalt has been applied to prevent volume changes, with the asphalt serving as both a conductive material and a binder. However, depending on the type of asphalt used, there is an issue of inconsistent performance in the secondary battery. Summary of the Invention
[0006] Technical issues The present invention aims to overcome the above-mentioned problems. The purpose of the present invention is to provide a coating composition for coating the surface of a secondary battery electrode active material and a secondary battery electrode material including the coating composition. In this invention, by forming a coating layer including petroleum asphalt with a softening point of 200°C to 270°C on the surface of the electrode active material, the crystal structure and / or coating uniformity of the coating layer are ensured, thereby significantly improving the performance of the secondary battery using the electrode material, especially its lifespan characteristics.
[0007] Technical solution To address the aforementioned problems, the coating composition according to the present invention for coating the surface of active materials for secondary battery electrodes may include: petroleum asphalt with a softening point of 200°C to 270°C; and volatiles that volatilize at a temperature of 300°C or lower.
[0008] In a preferred embodiment of the present invention, petroleum asphalt may include isotropic petroleum asphalt and anisotropic petroleum asphalt.
[0009] In a preferred embodiment of the invention, based on the total weight%, the coating composition according to the invention for coating the surface of the active material of the secondary battery electrode may include volatiles that volatilize at 300°C or lower in an amount of 10.0% by weight or less.
[0010] In a preferred embodiment of the present invention, based on the total weight percentage, the coating composition according to the present invention for coating the surface of the active material of the secondary battery electrode may include 80% to 99% by weight of isotropic petroleum bitumen and 1% to 20% by weight of anisotropic petroleum bitumen.
[0011] In a preferred embodiment of the present invention, the secondary battery may be a lead (Pb) battery, a nickel-cadmium (NiCd) battery, a nickel metal (Ni metal) hydride battery, a lithium-ion (Li-ion) battery, a solid-state battery, a soft carbon battery, a hard carbon battery, or a lithium-ion polymer (Li-ion polymer) battery.
[0012] In a preferred embodiment of the present invention, the electrode active material may be a negative electrode active material.
[0013] In a preferred embodiment of the present invention, the negative electrode active material may include silicon (Si).
[0014] Meanwhile, the secondary battery electrode material of the present invention may include: a silicon-containing electrode active material; and a coating layer coated on the surface of the electrode active material.
[0015] In a preferred embodiment of the present invention, the coating layer may be formed by carbonizing a coating composition according to the present invention for coating the surface of a secondary battery electrode active material.
[0016] In a preferred embodiment of the present invention, the secondary battery electrode material of the present invention may include a coating layer in an amount of 2.1% to 10.0% by weight, based on the total weight percentage.
[0017] In a preferred embodiment of the invention, the coating layer may include carbonized petroleum bitumen.
[0018] In a preferred embodiment of the present invention, petroleum asphalt may include isotropic petroleum asphalt and anisotropic petroleum asphalt.
[0019] In a preferred embodiment of the present invention, the carbonized petroleum asphalt may be carbonized at a temperature of 600°C to 800°C for 30 to 120 minutes.
[0020] In a preferred embodiment of the present invention, the electrode active material may include a non-porous carbon support, which includes any one or more of hard carbon and soft carbon.
[0021] In a preferred embodiment of the present invention, the electrode active material may include a porous carbon support, and silicon may be disposed on the surface of the porous carbon support and inside the pores.
[0022] In a preferred embodiment of the invention, the secondary battery electrode material may include silicon in an amount ranging from 30.0% to 80.0% by weight, based on the total weight percentage.
[0023] Beneficial effects In the coating composition for coating the surface of the active material of a secondary battery electrode according to the present invention and the secondary battery electrode material including the coating composition, by forming a coating layer including petroleum asphalt with a softening point of 200°C to 270°C on the surface of the active material, the crystal structure and / or coating uniformity of the coating layer are ensured, thereby significantly improving the performance of the secondary battery using the electrode material, especially its lifespan characteristics. Detailed Implementation
[0024] The invention will be described in more detail below.
[0025] Previously, when using anode materials such as silicon, a technique of coating the surface of the anode material with asphalt was employed to prevent volume changes. The asphalt served as both a conductive material and a binder. However, depending on the type of asphalt used, there was an issue of inconsistent performance in the secondary battery.
[0026] Therefore, in this invention, by forming a coating layer comprising petroleum asphalt with a softening point of 200°C to 270°C on the surface of the electrode active material, the crystal structure and coating uniformity of the coating layer are ensured, thereby significantly improving the performance of secondary batteries using this electrode active material, especially its lifespan characteristics.
[0027] The coating composition of the present invention for coating the surface of active materials for secondary battery electrodes may include bitumen and volatile substances.
[0028] Asphalt is an organic material that is solid at room temperature or is a residue from the pyrolysis of tar distillation. It is composed of a complex mixture of many highly aromatic hydrocarbons and heterocyclic compounds. Asphalt is not a substance with a constant melting point, but rather has a wide softening range, with softening temperatures ranging from about 320 K to about 570 K depending on molecular weight and composition.
[0029] The asphalt of the present invention may include one or more selected from petroleum asphalt, coal tar pitch and mesomorphic pitch, and may preferably include petroleum asphalt.
[0030] Specifically, the asphalt of the present invention may include petroleum asphalt, and may preferably include petroleum asphalt with a softening point of 200°C to 270°C, more preferably 220°C to 270°C, even more preferably 240°C to 260°C, and even more preferably 250°C to 260°C. If the softening point is less than 200°C, there may be problems not only in preparing asphalt for introduction into the dry coating process (mechanical fusion), but also in the asphalt clumping at low temperatures or melting due to frictional heat generated by the rotation speed (rpm) of the inner wall during carbonization; and if the softening point is greater than 270°C, there may be problems with the uniformity of asphalt coating.
[0031] In addition, petroleum bitumen can include isotropic petroleum bitumen and anisotropic petroleum bitumen.
[0032] Specifically, based on total wt%, the coating composition according to the invention for coating the surface of the active material of a secondary battery electrode may include isotropic petroleum asphalt in an amount of 80 wt% to 99 wt%, preferably 82 wt% to 97 wt%, more preferably 84 wt% to 97 wt%, even more preferably 88 wt% to 97 wt%, and even more preferably 92 wt% to 97 wt%. If the isotropic petroleum asphalt is included in an amount of less than 80 wt%, there may be a problem of forming an uneven coating layer, and if it is included in an amount of more than 99 wt%, there may be a problem of reduced conductivity.
[0033] Furthermore, based on the total weight percentage, the coating composition according to the invention for coating the surface of the active material of a secondary battery electrode can include anisotropic petroleum asphalt in an amount of 1% to 20% by weight, preferably 1.2% to 15% by weight, more preferably 1.5% to 10% by weight, even more preferably 2.0% to 7.0% by weight, and even more preferably 2.0% to 4.0% by weight. If the anisotropic petroleum asphalt is included in an amount of less than 1% by weight, there may be a problem of reduced conductivity, and if it is included in an amount of more than 20% by weight, there may be a problem of forming an uneven coating layer.
[0034] In addition, volatile components can include components that volatilize at temperatures of 300°C or lower as volatile substances.
[0035] Specifically, based on the total weight percentage, the coating composition according to the invention for coating the surface of the active material of a secondary battery electrode may include volatiles that volatilize at 300°C or lower in an amount of 10.0% by weight or less, preferably from 0.1% by weight to 10% by weight, more preferably from 0.3% by weight to 8.0% by weight, even more preferably from 0.5% by weight to 5.0% by weight, and even more preferably from 0.5% by weight to 2.0% by weight. If the volatiles are included in an amount greater than 10% by weight, there may be a problem of forming an uneven coating layer.
[0036] Meanwhile, in the coating composition according to the present invention for coating the surface of a secondary battery electrode active material, the value calculated by the following formula 1 can be 0.8 or less, preferably 0.3 to 0.8, more preferably 0.3 to 0.75, even more preferably 0.35 to 0.7, and even more preferably 0.4 to 0.6. If the value calculated by the following formula 1 is greater than 0.8, the degree of polymerization of the asphalt contained in the coating composition of the present invention for coating the surface of a secondary battery electrode active material may decrease, and there may be a problem that the softening point is not met as intended by the present invention.
[0037] [Relation 1] S / S P × 100 + MP In Equation 1 above, S represents the mass ratio of saturated hydrocarbons (saturated fractions) in the coating composition used to coat the surface of the active material of the secondary battery electrode, as determined by saturates-aromatics-resins-asphaltenes (SARA) analysis. P MP represents the softening point of the coating composition used to coat the surface of the active material of the secondary battery electrode, and MP represents the volume ratio of the anisotropic petroleum asphalt content contained in the coating composition used to coat the surface of the active material of the secondary battery electrode.
[0038] In addition, the secondary battery of the present invention can be a lead (Pb) battery, a nickel-cadmium (NiCd) battery, a nickel metal (Ni metal) hydride battery, a lithium-ion (Li-ion) battery, a solid-state battery, a soft carbon battery, a hard carbon battery, or a lithium-ion polymer (Li-ion polymer) battery, and can preferably be a lithium-ion (Li-ion) battery.
[0039] In addition, the electrode active material of the present invention can be a negative electrode active material, and the negative electrode active material can include silicon (Si).
[0040] Furthermore, the secondary battery electrode material of the present invention may include a silicon-containing electrode active material and a coating layer covering the surface of the electrode active material.
[0041] In this paper, the electrode active material may include a silicon (Si)-containing porous carbon support, and silicon may be disposed on the surface and inside the pores of the porous carbon support. Specifically, a silicon (Si)-containing porous carbon support refers to a porous carbon support on which silicon is formed on the surface of an activated carbon porous carbon support, and the surface of the porous carbon support includes not only the surface exposed to the outside but also the surface located inside. Specifically, a porous carbon support is a porous material having pores on its outer surface and / or inner surface, and as an example, when silicon is used to coat the surface of a porous carbon support, silicon not only permeates through the pores and coats the outer surface of the porous carbon support but also permeates through the pores and coats the inner surface of the porous carbon support, thereby partially or completely sealing the pores of the porous carbon support, and may also coat the outer surface of the porous carbon support with a certain thickness.
[0042] Furthermore, when the electrode active material is a silicon (Si)-containing porous carbon support, the coating layer is formed on the surface of the silicon (Si)-containing porous carbon support. The surface of the silicon (Si)-containing porous carbon powder includes not only the exposed external surface but also the internal surface. Specifically, the silicon (Si)-containing porous carbon support is a porous material with pores on its outer and / or inner surfaces. As an example, when petroleum asphalt is used to form the coating layer, the petroleum asphalt not only permeates through the pores and coats the outer surface of the silicon (Si)-containing porous carbon support but also permeates through the pores and coats the inner surface of the silicon (Si)-containing porous carbon support, thereby partially or completely sealing the pores of the silicon (Si)-containing porous carbon support. It can also coat the outer surface of the silicon (Si)-containing porous carbon support with a certain thickness to form the coating layer.
[0043] In addition, the electrode active material may include a non-porous carbon support, which includes any one or more of hard carbon and soft carbon.
[0044] In addition, the preferred electrode active material is a carbon-silicon composite material.
[0045] The carbon-silicon composite material includes a carbon support and silicon (Si), the carbon support includes a surface layer portion and a core portion, and the silicon (Si) is disposed on the surface of the carbon support and includes the surface of the carbon support.
[0046] In this specification, the core portion of a carbon support may refer to the area within half the radius of the support from the center, and the surface layer portion may refer to the remaining area of the support excluding the core portion.
[0047] As a porous carbon support, any carbon support commonly used in the art can be used without limitation. However, it is preferable to use any one or more of non-porous carbon supports and porous carbon supports. More preferably, it is preferable to use any one or more of graphite, hard carbon, soft carbon and porous carbon supports. Even more preferably, using any one or more of hard carbon, soft carbon and porous carbon supports is more conducive to achieving the purpose of the present invention.
[0048] When the carbon support is a porous carbon support, the porous carbon support can be prepared by a method comprising the following steps: (1) synthesizing asphalt by pyrolysis and polycondensation of petroleum-based feedstock; (2) curing and granulating the asphalt to obtain granular asphalt, or curing, granulating and pulverizing the asphalt to obtain powdered asphalt; (3) stabilizing the granular or powdered asphalt; (4) carbonizing the stabilized asphalt to obtain a carbide; and (5) activating the carbide to obtain a porous carbon support.
[0049] In the method for preparing a porous carbon support according to the present invention, step (1) may be a step of synthesizing asphalt by pyrolysis and polycondensation of petroleum-based feedstock.
[0050] In embodiments of the present invention, the petroleum-based feedstock may include at least one selected from the group consisting of pyrolysis fuel oil (PFO), naphtha cracking bottom oil (NCB), ethylene cracker bottom oil (EBO), vacuum residue (VR), deasphalted oil (DAO), atmospheric residue (AR), fluid catalytic cracking decant oil (FCC-DO), residue fluid catalytic cracking decant oil (RFCC-DO), and heavy aromatic oil. In a preferred embodiment of the present invention, the petroleum-based feedstock may include pyrolysis fuel oil.
[0051] In embodiments of the present invention, the petroleum-based feedstock may contain aromatic compounds in an amount of 10% to 90% by weight. Preferably, the petroleum-based feedstock may contain aromatic compounds in an amount of 20% to 80% by weight, and more preferably in an amount of 30% to 70% by weight. When the content of aromatic compounds in the petroleum-based feedstock meets the above ranges, a porous carbon support with controlled pore characteristics can be obtained even if the solid asphalt particles are stabilized, carbonized, and activated without separate pulverization, wherein the solid asphalt particles will be described below.
[0052] In embodiments of the present invention, the aromatic compound may be a compound having one to four aromatic rings. Specifically, the aromatic compound may include at least one selected from substituted or unsubstituted benzene, naphthalene, phenanthrene, indene, biphenyl, anthracene, tetrahydronaphthalene, and fluorene. In this case, even if the solid asphalt aggregate is stabilized, carbonized, and activated without separate pulverization, a porous carbon support with controlled pore properties can be obtained, wherein the solid asphalt aggregate will be described below.
[0053] In embodiments of the present invention, the pyrolysis and polycondensation of petroleum-based feedstocks can be carried out at a temperature of 350°C to 500°C. In a preferred embodiment of the present invention, the pyrolysis and polycondensation of petroleum-based feedstocks can be carried out at a temperature of 400°C to 500°C. In a more preferred embodiment of the present invention, the pyrolysis and polycondensation of petroleum-based feedstocks can be carried out at a temperature of 430°C to 470°C. When the pyrolysis and polycondensation temperature of the petroleum-based feedstocks is 350°C to 500°C, asphalt containing a large amount of relatively low molecular weight components can be prepared, and during the activation process in step (5) described below, the relatively low molecular weight components first vaporize, allowing sufficient mesopores to be formed in the carbon support. If the pyrolysis and polycondensation temperature of the petroleum-based feedstocks is below 350°C, it is difficult to prepare asphalt that is solid at room temperature, and if the temperature is above 500°C, the asphalt contains a large amount of relatively high molecular weight components, making it difficult to prepare a carbon support with mesopores.
[0054] In embodiments of the present invention, the pyrolysis and polycondensation of petroleum-based feedstocks can be carried out in an atmosphere of an oxidizing gas, an inert gas, or a mixture thereof. In a preferred embodiment of the present invention, the oxidizing gas can be oxygen, ozone, or a combination thereof, the inert gas can be nitrogen, helium, neon, argon, or a combination thereof, and a mixture thereof can be air, but they are not particularly limited thereto.
[0055] When oxidizing gases are used in the pyrolysis and polycondensation of petroleum-based feedstocks, asphalt with a high softening point can be prepared, but it is difficult to carry out pyrolysis and polycondensation at high temperatures. When inert gases are used in the pyrolysis and polycondensation of petroleum-based feedstocks, pyrolysis and polycondensation can be carried out at relatively high temperatures to prepare asphalt with a relatively high softening point. When a mixture of oxidizing and inert gases is used in the pyrolysis and polycondensation of petroleum-based feedstocks, pyrolysis and polycondensation can be carried out at relatively high temperatures to prepare asphalt with a relatively high softening point.
[0056] In embodiments of the invention, the gas can be supplied at a flow rate of 10 mL / min to 800 mL / min during the pyrolysis and polycondensation of the petroleum-based feedstock. In a preferred embodiment of the invention, the gas can be supplied at a flow rate of 100 mL / min to 500 mL / min during the pyrolysis and polycondensation of the petroleum-based feedstock. If the flow rate of the gas is less than 10 mL / min, the yield of asphalt increases, but the amount of low molecular weight components becomes excessive, which is detrimental to subsequent processes (e.g., stabilization). If the flow rate of the gas is greater than 800 mL / min, the yield of asphalt may decrease.
[0057] In embodiments of the present invention, the pyrolysis and polycondensation of petroleum-based feedstocks can be carried out for 1 to 10 hours. In a preferred embodiment of the present invention, the pyrolysis and polycondensation of petroleum-based feedstocks can be carried out for 2 to 8 hours. In a more preferred embodiment of the present invention, the pyrolysis and polycondensation of petroleum-based feedstocks can be carried out for 2 to 7 hours. If the pyrolysis and polycondensation time of the petroleum-based feedstocks is less than 1 hour, it is difficult to prepare asphalt with a high softening point, and if the pyrolysis and polycondensation time of the petroleum-based feedstocks is greater than 10 hours, excessive quinoline-insoluble components may be generated.
[0058] In embodiments of the present invention, the pyrolysis and polycondensation of petroleum-based feedstocks can be carried out under stirring. There are no particular limitations on the stirring conditions for the petroleum-based feedstocks, but for example, a stirrer rotating at 10 rpm to 500 rpm can be used.
[0059] In embodiments of the present invention, the softening point of the asphalt synthesized in step (1) can be between 200°C and 350°C. In a preferred embodiment of the present invention, the softening point of the asphalt can be between 200°C and 330°C. In a more preferred embodiment of the present invention, the softening point of the asphalt can be between 200°C and 300°C. Because the asphalt prepared according to the present invention has a high softening point, when used as a precursor for preparing a carbon support, the stabilization process is easy, and a high yield can be obtained after carbonization and activation.
[0060] In an embodiment of the present invention, the yield of asphalt synthesized in step (1) may be from 10% to 50% by weight. In another embodiment of the present invention, the yield of asphalt may be from 10% to 40% by weight. In yet another embodiment of the present invention, the yield of asphalt may be from 20% to 30% by weight.
[0061] In the method for preparing a porous carbon support from petroleum-based raw materials according to an embodiment of the present invention, a pretreatment step of the petroleum-based raw materials can be performed before step (1) above. By removing low-boiling-point components contained in the petroleum-based raw materials through the pretreatment step, asphalt with a higher softening point can be prepared.
[0062] In embodiments of the present invention, the pretreatment step can be carried out at a temperature equal to or lower than the pyrolysis and polycondensation temperature of the petroleum-based raw material in step (1), but is not particularly limited to this condition. Specifically, the pretreatment step can be carried out at 250°C to 450°C, preferably 250°C to 400°C, and more preferably 300°C to 400°C.
[0063] In embodiments of the present invention, the pretreatment step may be carried out for a time equal to or shorter than the pyrolysis and polycondensation time of the petroleum-based feedstock in step (1), but is not particularly limited to this condition. Specifically, the pretreatment step may be carried out for 1 to 8 hours, preferably 1 to 6 hours, and more preferably 1 to 5 hours.
[0064] In addition, in step (2), the asphalt can be cured and granulated to obtain granular asphalt, or the asphalt can be cured, granulated and crushed to obtain powdered asphalt.
[0065] First, in the case of granular asphalt, the liquid asphalt obtained in step (1) is solidified, for example, by extrusion and cooling, and granulated to the desired size to obtain solid asphalt aggregate (granular asphalt). The process of extruding, cooling, and granulating liquid asphalt to obtain solid asphalt aggregate can be carried out using commercially available equipment. For example, the process can be carried out using a dual-belt cooler and sheet forming machine from IPCO, but is not particularly limited to this equipment.
[0066] The average particle size of the asphalt aggregate (granular asphalt) obtained in step (2) is 1 mm to 30 mm, and preferably 5 mm to 25 mm. When the average particle size of the asphalt aggregate (granular asphalt) is within this range, a porous carbon support can be prepared by stabilization, carbonization and activation as described below without separately crushing the asphalt aggregate (granular asphalt).
[0067] Furthermore, in the case of powdered asphalt, asphalt aggregates (granular asphalt) can be further crushed or pulverized and classified. Crushing or pulverizing further micronizes the asphalt aggregates (granular asphalt), while classification ensures a uniform particle size distribution. Here, dry classification, wet classification, or sieve classification can be used for classification. Through crushing or pulverizing and classification, powdered asphalt with a diameter of 50 μm to 500 μm can be obtained.
[0068] Then, in step (3), a stabilization step can be performed on the granular or powdered asphalt. Specifically, step (3) can be a step of initially oxidizing the granular or powdered asphalt to stabilize the structure of the asphalt.
[0069] In embodiments of the invention, asphalt stabilization can be carried out at temperatures ranging from 100°C to 500°C, and preferably from 150°C to 350°C. When asphalt stabilization is carried out at these temperatures, the carbon structure in granular or powdered asphalt changes from thermoplastic to thermosetting, allowing this structure to be stably maintained during the subsequent carbonization process. In this case, the temperature rise rate can be from 2°C / min to 10°C / min. If the temperature rise rate is too slow, productivity is poor; and if the temperature rise rate is too fast, uniform stabilization may be difficult.
[0070] In embodiments of the invention, stabilization can be carried out at a pressure of 0.1 bar to 10 bar, and preferably 0.5 bar to 5 bar. When stabilization is carried out at this pressure, the stabilization of the structure can be sufficiently carried out to the extent that the carbon inside the granular or powdered asphalt is also stabilized.
[0071] In embodiments of the invention, stabilization can be carried out under a flow rate of oxidizing gas, preferably air or oxygen, from 0.1 mL / min to 500 mL / min, and preferably from 1 mL / min to 300 mL / min. When stabilization is carried out under this oxidizing gas flow rate, the stabilization of the structure can be sufficiently carried out to the extent that the carbon inside the granular or powdered asphalt is also stabilized.
[0072] In embodiments of the present invention, stabilization can be carried out for a period of 1 to 10 hours, and preferably 2 to 8 hours. When stabilization is carried out for this period of time, the stabilization of the structure can be carried out sufficiently to the extent that the carbon inside the granular or powdered asphalt is also stabilized.
[0073] Then, in step (4), the stabilized asphalt can be carbonized to obtain a carbide. By carbonizing the stabilized asphalt, other functional groups contained in the asphalt are removed, and a carbide composed of essentially pure carbon can be obtained.
[0074] In embodiments of the present invention, carbonization can be carried out under an inert gas atmosphere. In a preferred embodiment of the present invention, asphalt carbonization can be carried out under a nitrogen or argon atmosphere, but is not particularly limited thereto.
[0075] In embodiments of the invention, carbonization can be carried out at a temperature of 700°C to 1,000°C, preferably 800°C to 1,000°C. If the temperature during carbonization is below this range, carbonization may not be sufficiently achieved, and if the temperature during carbonization is above this range, the carbonization yield may be reduced.
[0076] In embodiments of the invention, carbonization can be carried out under inert gas flow rates of 0.1 mL / min to 30 mL / min, and preferably 0.1 mL / min to 10 mL / min, preferably nitrogen. When carbonization is carried out under these inert gas flow rate conditions, the stabilized asphalt can be fully carbonized.
[0077] In embodiments of the present invention, carbonization can be carried out for 0.5 to 5 hours, and preferably 1 to 3 hours. During this carbonization period, the stabilized asphalt can be fully carbonized.
[0078] Then, in step (5), the carbide (carbonized bitumen) can be activated to obtain a porous carbon support. By activating the carbide (carbonized bitumen), pores are formed in the bitumen, thereby obtaining a porous carbon support.
[0079] In embodiments of the present invention, the activation of the carbide can be carried out in an oxidizing gas atmosphere. In a preferred embodiment of the present invention, the activation of the carbide can be carried out in a vapor atmosphere, but is not particularly limited thereto.
[0080] In embodiments of the present invention, the activation of the carbide can be carried out at a temperature of 700°C to 1,000°C, or 800°C to 1,000°C. When the carbide is activated at this temperature, a porous carbon support with sufficiently formed micropores and mesopores can be obtained.
[0081] In embodiments of the present invention, activation of the carbide can be carried out at a pressure of 0.1 bar to 10 bar, and preferably 0.1 bar to 5 bar. When the carbide is activated at this pressure, a porous carbon support with sufficiently formed micropores and mesopores can be obtained.
[0082] In embodiments of the present invention, activation of the carbide can be carried out under conditions of an oxidizing gas flow rate of 0.1 mL / min to 100 mL / min, and preferably 0.1 mL / min to 50 mL / min, preferably vapor. When the carbide is activated under these oxidizing gas flow rate conditions, a porous carbon support with sufficiently formed micropores and mesopores can be obtained.
[0083] In embodiments of the present invention, the activation of the carbide can be carried out for 0.5 hours to 5 hours, and preferably 1 hour to 3 hours. When the activation of the carbide is carried out for this period of time, a porous carbon support with sufficiently formed micropores and mesopores can be obtained.
[0084] In embodiments of the present invention, the stabilization, carbonization, and activation of steps (3) to (5) above can each be performed in a microwave-heated furnace. In a preferred embodiment of the present invention, the stabilization, carbonization, and activation of steps (3) to (5) above can all be performed in a microwave-heated furnace. A microwave-heated furnace is preferred because it can raise the temperature of the asphalt itself without raising the external temperature of the asphalt, but is not particularly limited thereto.
[0085] In embodiments of the present invention, the stabilization, carbonization, and activation of steps (3) to (5) above can be performed continuously in one apparatus. In a preferred embodiment of the present invention, the stabilization, carbonization, and activation of steps (3) to (5) above can be performed continuously in one rotary kiln, but the apparatus is not particularly limited thereto. By performing stabilization, carbonization, and activation continuously in one apparatus, process optimization can be easily achieved.
[0086] In embodiments of the present invention, the porous carbon support (or porous carbon support powder) obtained in step (5) can be further crushed or pulverized and classified. Crushing or pulverizing allows for further micronization of the porous carbon support powder, and classification ensures a uniform particle size distribution. Here, dry classification, wet classification, or sieve classification can be used for classification. Through crushing or pulverizing and classification, a powdered porous carbon support with a diameter of 1 μm to 20 μm can be obtained.
[0087] The porous carbon support prepared by performing steps (1) to (5) above includes mesopores with a diameter of 2 nm to 50 nm, and the ratio of the volume of the mesopores in the surface layer portion to the total volume of the mesopores can be 0.5 or greater, and preferably 0.5 to 0.76. When the ratio of the mesopores in the surface layer portion to the total mesopores in the porous carbon support is 0.5 or greater, the mesopores formed in the surface layer portion act as channels through which pores can be formed to the core portion, allowing silicon to be deposited into the interior of the support. Furthermore, the total volume of the mesopores in the porous carbon support can refer to the volume of all the mesopores disposed inside the porous carbon support, and the volume of the mesopores in the surface layer portion can refer to the volume of all the mesopores disposed in the surface layer portion of the porous carbon support. Furthermore, the volume of the mesopores in the surface layer portion can refer to the volume of the region corresponding to the surface layer portion relative to all the mesopores disposed in the porous carbon support.
[0088] In this case, if the ratio of mesopores in the surface layer portion to the total mesopores of the carbon-silicon composite particles is outside the above range, the charge / discharge capacity may decrease and the cycle characteristics may deteriorate.
[0089] In one example of the invention, in the porous carbon support of the carbon-silicon composite material according to the invention, the ratio of the volume of mesopores to the total volume of pores can be 0.1 or greater. The pores of the porous carbon support can be classified according to their size as micropores with a diameter less than 2 nm, mesopores with a diameter from 2 nm to 50 nm, and macropores with a diameter greater than 50 nm. Such porous supports have been studied in the direction of increasing the ratio of micropores to increase the specific surface area, or increasing the ratio of macropores to increase the amount of material loaded inside the pores. However, when many micropores are present, silicon (Si) is difficult to deposit inside the pores, leading to a problem of reduced capacitance. Furthermore, when many macropores are present, silicon agglomeration occurs, which generates stress during repeated charge / discharge processes and may mechanically damage the anode material.
[0090] On the other hand, in the case of mesopores, silicon can be sufficiently deposited deep into the pores during deposition. The carbon-silicon composite particles according to the invention include mesopores within a predetermined range, such that a sufficient amount of silicon can be deposited inside the pores of the porous carrier.
[0091] Furthermore, the porosity of the surface layer portion of the porous carbon support can be greater than that of the core portion, which is more conducive to achieving the objectives of this invention.
[0092] In porous carbon supports, the ratio of mesopore volume to total pore volume can be 0.10 or greater, 0.12 or greater, 0.14 or greater, or 0.15 or greater, but is not limited to these values. There is no particular upper limit to the ratio of mesopore volume to total pore volume in porous carbon supports, but it can be 0.7 or less. When the ratio of mesopore volume to total pore volume in porous carbon supports meets the above ranges, excellent electrical properties can be obtained while preventing excessive silicon agglomeration, thereby preventing damage caused by silicon volume expansion.
[0093] In embodiments of the present invention, the tap density of the porous carbon support can be 0.7 g / mL or less. The tap density of the porous carbon support can be a value measured using a PT-TD200 (Pharma Test). Specifically, 40 mL of porous carbon support is loaded into a cylinder, tapped 1000 times, and then the first volume is observed. After observation, the process of tapping 1000 times again and observing the volume is repeated three times until there is no difference from the previous volume. Then, the tap density can be calculated from the final volume. The tap density of the porous carbon support can be 0.70 g / mL or less, 0.65 g / mL or less, or 0.60 g / mL or less, and can be 0.05 g / mL or more, 0.10 g / mL or more, 0.15 g / mL or more, 0.20 g / mL or more, or 0.22 g / mL or more, but is not limited thereto. If the tap density of the porous carbon support is too low, process control during silane gas deposition may be difficult, resulting in a lower yield. Furthermore, if the tap density of the porous carbon support is too high, uniform coating during silane gas deposition may be difficult.
[0094] In one example of the invention, the Brunauer-Emmett-Teller (BET) specific surface area of the porous carbon support according to the invention can reach 200 m². 2 / g to 3,000 m 2 The BET specific surface area of the porous carbon support can be measured using an ASAP 2420 (Micromeritics Instruments, USA). Specifically, analysis is performed after vacuum drying at 300 °C for 5 hours, and the value can be calculated using the BET equation and the BJH equation based on the adsorption results from the N2 / 77 K isotherm, according to ISO 9277. The BET specific surface area of the porous carbon support can be 200 m² / g. 2 / g or greater, 400 m 2 / g or greater, or 500 m 2 / g or greater, and can be 3,000 m 2 / g or less, 2,800 m 2 / g or less, 2,600 m 2 / g or less, 2,000 m 2 / g or less, or 1,900 m 2 / g or less, but not limited to this. If the BET specific surface area of the porous carbon support is too low, the ratio of macropores increases, which may reduce the mechanical strength of the anode material, and the effective pores may be insufficient. In addition, if the BET specific surface area of the porous carbon support is too high, the ratio of micropores may increase, and silicon may not be able to be sufficiently deposited into the core portion of the porous carbon support.
[0095] The diameter of porous carbon supports can be 20 μm or smaller. Diameter can refer to D... 50 The diameter can be a value measured using a MICROTRAC S3500 instrument. Specifically, it can refer to the average value obtained by dispersing a porous carbon support in ethanol and then performing three particle size analyses. The diameter of the porous carbon support can be 20 μm or less, 18 μm or less, 16 μm or less, 14 μm or less, 12 μm or less, or 10 μm or less, and can be 1 μm or more, 2 μm or more, 3 μm or more, 4 μm or more, or 4.5 μm or more, but is not limited to these. If the diameter of the porous carbon support is too small, its interior will be rapidly filled with silicon during coating, followed by additional coating on the surface portion, resulting in a thick surface coating layer. In this case, degradation during charge / discharge may be accelerated, agglomeration of materials with small particle sizes may occur during electrode fabrication, and the agglomerated portions may exhibit significant degradation. Furthermore, if the diameter of the porous carbon support is too large, silane gas will have difficulty diffusing into the interior of the porous carbon support, making it difficult to form a uniform silicon coating layer inside the support. In addition, if the diameter of the porous carbon support is too large, it will be difficult to uniformly coat the slurry onto the current collector during electrode fabrication, which may reduce the uniformity of capacity.
[0096] In one example, the porous carbon support of the carbon-silicon composite material according to the present invention may include macropores with a diameter greater than 50 nm. In this case, the ratio of the volume of the macropores to the total volume of the pores in the porous carbon support may be 0.4 or less. The ratio of the volume of the macropores to the total volume of the pores in the porous carbon support may be 0.40 or less, 0.35 or less, 0.30 or less, 0.25 or less, 0.20 or less, or 0.15 or less, but is not limited thereto. There is no particular limitation on the lower limit of the ratio of the volume of the macropores to the total volume of the pores in the porous carbon support, but it may be, for example, 0 or greater, or greater than 0. If the ratio of macropores in the porous carbon support of the carbon-silicon composite material is too high, the mechanical strength of the anode material made of the carbon-silicon composite material may be reduced. In addition, local agglomeration of silicon occurs inside the anode material, and stress is generated due to volume expansion during repeated charge / discharge processes, which may lead to damage to the anode material.
[0097] In addition, when the carbon carrier is hard carbon, hard carbon can be prepared by a method including the following steps: (1') synthesizing asphalt by pyrolysis and polycondensation of petroleum-based feedstock; (2') curing and granulating the asphalt to obtain granular asphalt, or curing, granulating and pulverizing the asphalt to obtain powdered asphalt; (3') stabilizing the granular or powdered asphalt; and (4') carbonizing the stabilized asphalt to obtain hard carbon.
[0098] Here, since the descriptions of steps (1') to (4') can be the same as those of steps (1) to (4) above, their detailed descriptions will be omitted.
[0099] Meanwhile, the asphalt used to prepare hard carbon can be any one or more of isotropic and anisotropic asphalt, and the asphalt is preferably isotropic asphalt, which is more advantageous for achieving the purpose of the present invention.
[0100] Furthermore, when the carbon carrier is soft carbon, the soft carbon can be prepared by a method comprising the following steps: (1'') synthesizing asphalt by pyrolysis and polycondensation of petroleum-based feedstock; (2'') curing and granulating the asphalt to obtain granular asphalt, or curing, granulating and pulverizing the asphalt to obtain powdered asphalt; (3'') stabilizing the granular or powdered asphalt; and (4'') carbonizing the stabilized asphalt to obtain soft carbon.
[0101] In this case, since the descriptions of steps (1'') and (2'') can be the same as those of steps (1) and (2) above, their detailed descriptions will be omitted.
[0102] As in steps (3) and (4) above, the steps (3'') and (4'') described below can be carried out as a series of steps in a rotary kiln, or by placing the material in a crucible and placing the crucible into the furnace as a series of steps. Preferably, carrying out the series of steps by placing the material in a crucible and placing the crucible into the furnace can help achieve the purpose of the present invention.
[0103] Meanwhile, apart from the above, the description of the content of step (3'') can be the same as the description of step (3) above, so its detailed description will be omitted.
[0104] Furthermore, step (4'') is the step of carbonizing the stabilized bitumen to obtain soft carbon. By carbonizing the stabilized bitumen, other functional groups contained in the bitumen are removed, and soft carbon composed of essentially pure carbon can be obtained.
[0105] In an embodiment of the present invention, the carbonization in step (4'') can be carried out under an inert gas atmosphere. In a preferred embodiment of the present invention, the carbonization in step (4'') can be carried out under a nitrogen or argon atmosphere, but is not particularly limited thereto.
[0106] In embodiments of the present invention, the carbonization in step (4'') can be carried out at a temperature of 1,000°C to 2,700°C, and preferably 1,200°C to 2,200°C. If the temperature during carbonization in step (4'') is below this range, the development of the carbon crystal structure may not be sufficiently achieved, and if the temperature during carbonization is above this range, the carbonization yield may be reduced.
[0107] In embodiments of the present invention, the carbonization in step (4'') can be carried out under inert gas flow rates of 0.1 mL / min to 30 mL / min, and preferably 0.1 mL / min to 10 mL / min, preferably argon. When carbonization is carried out under these inert gas flow rate conditions, the stabilized asphalt can be fully carbonized.
[0108] In embodiments of the present invention, the carbonization in step (4'') can be carried out for 0.5 hours to 5 hours, and preferably 1 hour to 3 hours. When the carbonization in step (4'') is carried out for this period of time, the stabilized asphalt can be fully carbonized.
[0109] Meanwhile, apart from the above, the description of the content of step (4'') can be the same as the description of step (4) above, so its detailed description will be omitted.
[0110] Meanwhile, the asphalt used to prepare soft carbon can be any one or more of isotropic and anisotropic asphalt, and the asphalt is preferably anisotropic asphalt, which is more advantageous for achieving the purpose of the present invention.
[0111] The coating layer of the present invention can be formed by carbonizing the coating composition used to coat the surface of the secondary battery electrode active material according to the present invention.
[0112] Furthermore, the coating layer of the present invention may include carbonized petroleum asphalt. Specifically, the coating layer may include isotropic petroleum asphalt and anisotropic petroleum asphalt.
[0113] More specifically, the coating layer can be formed by coating the surface of a silicon-containing electrode active material with a coating composition for coating the surface of the secondary battery electrode active material according to the present invention, followed by carbonization.
[0114] Meanwhile, the carbonized petroleum asphalt can be carbonized at a temperature of 600°C to 800°C, preferably 600°C to 750°C, and more preferably 650°C to 750°C for 30 to 120 minutes, preferably 30 to 60 minutes. If the carbonization temperature is below 600°C, the carbon crystal structure of the asphalt is not developed, resulting in low conductivity of the material, which may lead to a decrease in battery performance. Furthermore, if the carbonization temperature is above 800°C, silicon crystallizes, thus reducing conductivity and potentially reducing battery capacity. Additionally, if the carbonization time is less than 30 minutes, the degree of carbonization crystallization is low, which may reduce conductivity; and if the carbonization time is greater than 120 minutes, excessive heat treatment causes silicon crystallization, further reducing conductivity and potentially reducing battery capacity.
[0115] Furthermore, based on the total weight percentage, the secondary battery electrode material of the present invention may include silicon in an amount of 30.0% to 80.0% by weight, preferably 30.0% to 60.0% by weight, more preferably 30.0% to 41.0% by weight, even more preferably 33.0% to 40.0% by weight, even more preferably 35.0% to 40.0% by weight, and even more preferably 37.0% to 39.0% by weight.
[0116] Furthermore, based on the total weight percentage, the secondary battery electrode material of the present invention may include a coating layer in an amount of 2.1 wt% to 10.0 wt%, preferably 2.1 wt% to 6.0 wt%, more preferably 2.5 wt% to 5.0 wt%, and even more preferably 3.5 wt% to 5.0 wt%. If the coating layer is included in an amount less than 2.1 wt%, there may be a problem of forming an uneven coating layer, and if the coating layer is included in an amount greater than 10.0 wt%, there may be a problem of reduced capacity due to the formation of too much coating layer.
[0117] Furthermore, the specific surface area of the secondary battery electrode material of the present invention can be 70 m². 2 / g or less, preferably 10m 2 / g to 70m 2 / g, more preferably 20m 2 / g to 60m 2 / g, and preferably 30m 2 / g to 50m 2 / g. If the specific surface area exceeds 70m² 2 If the value is / g, there may be a problem with reduced lifespan.
[0118] Furthermore, the pore volume of the secondary battery electrode material of the present invention can be 0.12 cm³. 3 / g or less, preferably 0.01cm 3 / g to 0.12cm 3 / g, more preferably 0.02cm 3 / g to 0.1cm 3 / g, and more preferably 0.03cm 3 / g to 0.08cm 3 / g. If the pore volume is greater than 0.12cm³. 3 If the value is / g, there may be a problem with reduced lifespan.
[0119] Furthermore, the D of the secondary battery electrode material of the present invention 50 The diameter can be 20 μm or smaller, preferably 2 μm to 15 μm, more preferably 3 μm to 10 μm, and even more preferably 4 μm to 8 μm. If D 50 If the diameter is greater than 20 μm, the large particles in the active material may cause uneven coating during electrode manufacturing, which may lead to problems that prevent electrode manufacturing from proceeding.
[0120] Furthermore, the tap density of the secondary battery electrode material of the present invention can be 0.1 g / cm³. 3 Up to 10g / cm 3 The preferred value is 0.2 g / cm³. 3 Up to 5g / cm 3 More preferably 0.3 g / cm 3 Up to 1g / cm 3 Furthermore, it is even more preferred to be 0.4 g / cm³. 3 Up to 0.8 g / cm 3 If the tapped density is less than 0.1 g / cm³ 3 Using excessive amounts of electrode active material may lead to an increase in the thickness of the electrode material, especially if the tap density is greater than 10 g / cm³. 3 If this is not done, uneven coating may occur.
[0121] Meanwhile, the method for manufacturing the secondary battery electrode material according to the present invention includes a first step and a second step.
[0122] First, in the first step of the method for manufacturing the secondary battery electrode material according to the present invention, a coating composition according to the present invention for coating the surface of the secondary battery electrode active material may be applied to the surface of the electrode active material to form a coating layer on the surface of the electrode active material. Here, the electrode active material and / or the coating composition according to the present invention for coating the surface of the secondary battery electrode active material are the same as described above.
[0123] Alternatively, mechanical fusion can be used as a dry coating method.
[0124] Next, in the second step of the method for manufacturing the secondary battery electrode material according to the present invention, the electrode active material on which the coating layer is formed on the surface can be carbonized to manufacture the secondary battery electrode material.
[0125] Here, carbonization can be carried out at a temperature of 600°C to 800°C, preferably 600°C to 750°C, and more preferably 650°C to 750°C for 30 to 120 minutes, preferably 30 to 60 minutes.
[0126] The invention will be described in more detail below by way of examples, but the following examples do not limit the scope of the invention and should be interpreted as being intended to help understand the invention.
[0127] Preparation Example 1: Preparation of a coating composition for coating the surface of active materials for secondary battery electrodes (1) 300g of petroleum-based residue oil (YNCC, HTC PFO (pyrolysis fuel oil)) was introduced into a reactor equipped with a stirrer, and nitrogen was supplied at a flow rate of 100mL / min. Simultaneously, pyrolysis and polycondensation reactions were carried out to prepare petroleum asphalt. In this case, the stirrer was rotated at a speed of 200rpm, and the pyrolysis and polycondensation reactions were carried out at a temperature of 400°C for 3 hours.
[0128] (2) The prepared petroleum asphalt is solidified and granulated to prepare solid petroleum asphalt particles with an average particle size of 1 mm to 30 mm.
[0129] (3) The prepared solid petroleum asphalt particles were crushed, and then the crushed powder was introduced into a rotary kiln with three zones, in which stabilization, carbonization and activation were carried out in sequence. In this case, the carbonization yield of the stabilized powder was measured to be 63.2% by weight, which was measured using a thermogravimetric analysis (TGA) instrument after the temperature was raised to 900°C at a rate of 5°C / min.
[0130] (4) The activated powder is introduced back into the pulverizer (Netzsch, air jet mill) for re-pulverization to prepare a coating composition for coating the surface of the active material of the secondary battery electrode.
[0131] Preparation Example 2: Preparation of a coating composition for coating the surface of active materials for secondary battery electrodes A coating composition for coating the surface of a secondary battery electrode active material was prepared in the same manner as in Preparation Example 1. However, unlike Preparation Example 1, the pyrolysis and polycondensation reactions were carried out at 350°C for 3 hours, thereby finally preparing the coating composition for coating the surface of a secondary battery electrode active material.
[0132] Preparation Example 3: Preparation of a coating composition for coating the surface of active materials for secondary battery electrodes A coating composition for coating the surface of a secondary battery electrode active material was prepared in the same manner as in Preparation Example 1. However, unlike Preparation Example 1, the pyrolysis and polycondensation reactions were carried out at a temperature of 450°C for 3 hours, thereby finally preparing the coating composition for coating the surface of a secondary battery electrode active material.
[0133] Comparative Preparation Example 1: Preparation of a coating composition for coating the surface of active materials for secondary battery electrodes A coating composition for coating the surface of a secondary battery electrode active material was prepared in the same manner as in Preparation Example 1. However, unlike Preparation Example 1, the pyrolysis and polycondensation reactions were carried out at 300°C for 3 hours, thereby finally preparing the coating composition for coating the surface of a secondary battery electrode active material.
[0134] Comparative Preparation Example 2: Preparation of a coating composition for coating the surface of active materials for secondary battery electrodes A coating composition for coating the surface of a secondary battery electrode active material was prepared in the same manner as in Preparation Example 1. However, unlike Preparation Example 1, the pyrolysis and polycondensation reactions were carried out at a temperature of 500°C for 3 hours, thereby finally preparing the coating composition for coating the surface of a secondary battery electrode active material.
[0135] Experimental Example 1: SARA Analysis The coating compositions (=samples) prepared in Preparation Examples 1 to 3 and Comparative Preparation Examples 1 to 2 for coating the surfaces of active materials for secondary battery electrodes were analyzed for saturated aromatic-asphaltenes (SARA). Specifically, a Chromarod S-5 was loaded into a chromatographic rod holder, and a sample dissolved in dichloromethane (10 mg / mL to 15 mg / mL) was spotted onto it. Following the spotting guide, 1 μL of sample was added dropwise 7 to 8 times using a micropipette. After drying the chromatographic rod holder, it was placed in a container containing the developing solvent for development. In this case, hexane, toluene, and methanol / dichloromethane (5:95) were used as developing solvents in sequence. The dried chromatographic rod holder was mounted on an IATROSCAN MK-6, and a scan was performed for 30 seconds while the Clarity program was run on a connected PC, followed by analysis.
[0136] Experimental Example 2: Anisotropy Measurement The coating compositions for coating the surfaces of active materials for secondary battery electrodes prepared in Preparation Examples 1 to 3 and Comparative Preparation Examples 1 to 2 were subjected to high-temperature centrifugation. 0.6 g of the pulverized coating compositions for coating the surfaces of active materials for secondary battery electrodes prepared in Preparation Examples 1 to 3 and Comparative Preparation Examples 1 to 2 were placed in glass tubes with an inner diameter of 6 mm, an outer diameter of 8 mm, and a height of 90 mm to 100 mm. Two or four tubes were then mounted in a balanced manner inside a high-temperature centrifuge. The heater temperature of the high-temperature centrifuge was set to 410°C and increased at a rate of 15°C per minute. After approximately 30 minutes when the heater reached the target temperature, and when the actual internal temperature reached 350°C to 360°C, the centrifuge was performed at a speed of 1787 rpm to 3096 rpm (500 g to 1500 g) for 15 to 30 minutes. A tube containing a centrifuged coating composition for coating the surface of active materials for secondary battery electrodes was cut 23 mm to 28 mm from the bottom, cured together with epoxy resin, and then polished using a Tegramin-25 polisher. The polished cross-section was photographed using a polarizing microscope, and then the anisotropic / isotropic regions were manually specified using the ImageJ program, and the ratio of the anisotropic region to the total area was calculated.
[0137] Experimental Example 3: Determination of the physical properties of the coating composition used to coat the surface of the active material of a secondary battery electrode. Using experimental data measured in some of Experimental Examples 1 and 2, the softening point, constituent components and their contents of the coating compositions prepared in Preparation Examples 1 to 3 and Comparative Preparation Examples 1 to 2 for coating the surface of the active material of the secondary battery electrode were measured and are shown in Table 1 below. The values calculated by the following Equation 1 are also shown in Table 1 below.
[0138] [Relation 1] S / SP × 100 + MP In Equation 1 above, S represents the mass ratio of saturated hydrocarbons (saturated fractions) in the coating composition used to coat the surface of the active material of the secondary battery electrode, as determined by the saturated fraction-aromatic fraction-colloidal-asphaltene (SARA) analysis of Experimental Example 1. P MP represents the softening point of the coating composition used to coat the surface of the active material of the secondary battery electrode, and MP represents the volume ratio of the anisotropic petroleum asphalt content contained in the coating composition used to coat the surface of the active material of the secondary battery electrode.
[0139] [Table 1]
[0140] In Table 1 above, volatile matter is defined as the substance that volatilizes at 300°C or lower when thermogravimetric analysis (TGA) is performed under N2 atmosphere.
[0141] Preparation Example 4: Preparation of Silicon-Containing Electrode Active Materials As a silicon-containing electrode active material, a carbon-silicon composite material with silicon coated on the surface of a porous carbon support was prepared. This material has the physical properties listed in Table 2 below.
[0142] [Table 2]
[0143] Example 1: Manufacturing of secondary battery negative electrode materials (1) Using a mechanical fusion method, the coating composition prepared in Preparation Example 1 for coating the surface of the secondary battery electrode active material was dry coated onto the surface of the negative electrode active material to form a coating layer on the surface of the negative electrode active material. In this case, the silicon-containing electrode active material prepared in Preparation Example 4 was used as the negative electrode active material, and the coating was performed at a rotation speed of 4000 rpm for 15 minutes.
[0144] (2) Carbonize the negative electrode active material with a coating layer on its surface at 700°C for 60 minutes to manufacture a secondary battery negative electrode material.
[0145] Example 2: Manufacturing of secondary battery negative electrode materials The secondary battery negative electrode material was manufactured in the same manner as in Example 1. However, unlike Example 1, the coating composition prepared in Preparation Example 2 for coating the surface of the secondary battery electrode active material was used instead of the coating composition prepared in Preparation Example 1, thereby finally manufacturing the secondary battery negative electrode material.
[0146] Example 3: Manufacturing of secondary battery negative electrode materials The secondary battery negative electrode material was manufactured in the same manner as in Example 1. However, unlike Example 1, the coating composition prepared in Preparation Example 3 for coating the surface of the secondary battery electrode active material was used instead of the coating composition prepared in Preparation Example 1, thereby finally manufacturing the secondary battery negative electrode material.
[0147] Comparative Example 1: Manufacturing of secondary battery negative electrode materials The secondary battery negative electrode material was manufactured in the same manner as in Example 1. However, unlike Example 1, the coating composition for coating the surface of the secondary battery electrode active material prepared in Comparative Preparation Example 1 was used instead of the coating composition prepared in Preparation Example 1, thereby finally manufacturing the secondary battery negative electrode material.
[0148] Comparative Example 2: Manufacturing of secondary battery negative electrode materials The secondary battery negative electrode material was manufactured in the same manner as in Example 1. However, unlike Example 1, the coating composition for coating the surface of the secondary battery electrode active material prepared in Comparative Preparation Example 2 was used instead of the coating composition prepared in Preparation Example 1, thereby finally manufacturing the secondary battery negative electrode material.
[0149] Experiment Example 4: Determination of the physical properties of secondary battery negative electrode materials The specific surface area, pore volume, median particle size, tap density, silicon content, and coating content of the secondary battery anode materials manufactured in Examples 1 to 3 and Comparative Examples 1 to 2 were measured and are shown in Table 3 below. Simultaneously, the coating content was calculated based on a curve obtained by measuring the temperature at a rate of 5°C / min when the temperature was increased to 900°C using a thermogravimetric analysis (TGA) instrument. The measured value was the maximum weight content (W) appearing at 500°C to 550°C. max Subtract the weight content (W) at the inflection point between 600℃ and 650℃ from the total weight. min The value obtained is the maximum weight content (W) that occurs at temperatures between 500°C and 550°C. max The weight content is due to the oxidation reaction of silicon contained in the negative electrode materials of each secondary battery manufactured in Examples 1 to 3 and Comparative Examples 1 to 2, and the point after 500°C is when the carbon contained in the negative electrode materials of each secondary battery manufactured in Examples 1 to 3 and Comparative Examples 1 to 2 is oxidized and removed. In the negative electrode materials of each secondary battery manufactured in Examples 1 to 3 and Comparative Examples 1 to 2, the coating layer was first removed by oxidation, and then the carbon support in the electrode active material was oxidized. Therefore, the weight content of the carbon layer was measured by utilizing the difference in thermal decomposition behavior between the coating layer and the electrode active material, thereby measuring the content of the coating layer.
[0150] [Table 3]
[0151] Manufacturing Example 1: Manufacturing of a secondary battery, specifically a button cell. (1) The secondary battery negative electrode material, conductive material and binder manufactured in Example 1 are mixed to prepare a negative electrode material slurry. In this case, based on a total amount of 100% by weight, 80% by weight of the secondary battery negative electrode material manufactured in Example 1, 10% by weight of the conductive material and 10% by weight of the binder are mixed to obtain the negative electrode material slurry, wherein conductive carbon black Super-P is used as the conductive material and a mixture of styrene-butadiene rubber (SBR) and sodium carboxymethyl cellulose (CMC) in a weight ratio of 5:5 is used as the binder.
[0152] (2) Prepare copper foil by uniformly coating the surface of the prepared copper foil with negative electrode material slurry and drying it in a vacuum oven at 120°C for 6 hours and 30 minutes to manufacture negative electrode plate.
[0153] (3) Prepare lithium foil. Use the prepared lithium foil and negative electrode plate as counter electrode and porous polyethylene film as separator. Stamp the mixture to obtain a secondary battery coin cell with a diameter of 20 mm and a thickness of 3.2 mm. In addition, inject electrolyte into the manufactured secondary battery coin cell. As electrolyte, use a 1.3 M LiPF6 solution dissolved in a mixed solution, which contains 10 wt% ethylene fluorocarbonate (FEC), 0.2 wt% lithium tetrafluoroborate (LiBF4), 0.5 wt% vinylene carbonate (VC) and 1 wt% propane sulfonate (PS) as additives. As the above mixed solution, use a mixture of 30 wt% ethylene carbonate (EC), 50 wt% ethyl methyl carbonate (EMC) and 20 wt% dimethyl carbonate (DMC) based on 100 vol% of the total volume.
[0154] Manufacturing Example 2: Manufacturing of Secondary Battery Button Cells The secondary battery coin cell was manufactured in the same manner as in Manufacturing Example 1. However, unlike Manufacturing Example 1, the secondary battery negative electrode material manufactured in Example 2 was used instead of the secondary battery negative electrode material manufactured in Example 1, thereby finally manufacturing the secondary battery coin cell.
[0155] Manufacturing Example 3: Manufacturing of Secondary Battery Button Cells The secondary battery coin cell was manufactured in the same manner as in Manufacturing Example 1. However, unlike Manufacturing Example 1, the secondary battery negative electrode material manufactured in Example 3 was used instead of the secondary battery negative electrode material manufactured in Example 1, thereby finally manufacturing the secondary battery coin cell.
[0156] Comparative Manufacturing Example 1: Manufacturing of Secondary Battery Button Cells The secondary battery coin cell was manufactured in the same manner as in Manufacturing Example 1. However, unlike Manufacturing Example 1, the secondary battery negative electrode material manufactured in Comparative Example 1 was used instead of the secondary battery negative electrode material manufactured in Example 1, thereby finally manufacturing the secondary battery coin cell.
[0157] Comparative Manufacturing Example 2: Manufacturing of Secondary Battery Button Cells The secondary battery coin cell was manufactured in the same manner as in Manufacturing Example 1. However, unlike Manufacturing Example 1, the secondary battery negative electrode material manufactured in Comparative Example 2 was used instead of the secondary battery negative electrode material manufactured in Example 1, thereby finally manufacturing the secondary battery coin cell.
[0158] Comparative Manufacturing Example 3: Manufacturing of Secondary Battery Button Cells The secondary battery coin cell was manufactured in the same manner as in Manufacturing Example 1. However, unlike Manufacturing Example 1, the silicon-containing electrode active material prepared in Preparation Example 4 was used instead of the secondary battery negative electrode material manufactured in Example 1, thereby finally manufacturing the secondary battery coin cell.
[0159] Experimental Example 5: Electrochemical Analysis The cutoff voltage (formulation: 0.005V to 1.5V, cycle test: 0.005V to 1.5V) and C-rate (formulation: 0.1 / 0.1, cutoff at 0.01C at 0.005V) of each secondary coin cell manufactured in Examples 1 to 3 and Comparative Examples 1 to 3 were measured, and the capacity (=charge capacity and discharge capacity), initial coulombic efficiency (ICE) and retention rate after 50 charge / discharge cycles were calculated respectively, and are shown in Tables 4 and 5 below.
[0160] [Table 4]
[0161] [Table 5]
[0162] As can be seen from Tables 4 and 5 above, the secondary coin cells manufactured in Examples 1 to 3 not only have excellent capacity, but also excellent initial coulombic efficiency (ICE), and excellent retention rate (= capacity retention rate) after 50 charge / discharge cycles.
[0163] Furthermore, among the secondary battery button cells manufactured in Examples 1 to 3, it can be confirmed that the secondary battery button cell manufactured in Example 1 has the best physical properties, and compared with the secondary battery button cell manufactured in Example 1, It was confirmed that the secondary coin cell half-cell manufactured in Comparative Manufacturing Example 1 exhibited deterioration in terms of capacity, ICE (internal capacity), and capacity retention. It was confirmed that the secondary coin cell half-cell manufactured in Comparative Manufacturing Example 2 exhibited deterioration in terms of capacity, ICE (internal capacity), and capacity retention. The secondary coin cell half-cell manufactured in Comparative Manufacturing Example 3 was found to have deteriorated capacity retention. This confirmed that the secondary coin cell half-cell manufactured in Manufacturing Example 2 exhibited slight degradation in ICE and capacity retention. It was confirmed that the secondary coin cell half-cell manufactured in Manufacturing Example 3 exhibited slight degradation in capacity, ICE, and capacity retention.
[0164] Specific embodiments have been described and illustrated above. However, the present invention is not limited to the above embodiments, and those skilled in the art will be able to make various modifications without departing from the spirit and intent of the invention as set forth in the appended claims.
Claims
1. A coating composition for coating the surface of an active material for a secondary battery electrode, the coating composition comprising: Petroleum bitumen, wherein the petroleum bitumen has a softening point of 200°C to 270°C; and Volatile components, which evaporate at a temperature of 300°C or lower.
2. The coating composition according to claim 1, wherein the petroleum bitumen comprises isotropic petroleum bitumen and anisotropic petroleum bitumen.
3. The coating composition of claim 1, wherein, based on total weight%, the coating composition includes volatiles that evaporate at a temperature of 300°C or lower in an amount of 10.0% by weight or less.
4. The coating composition according to claim 2, wherein, based on total weight%, the coating composition comprises 80% to 99% by weight of isotropic petroleum bitumen and 1% to 20% by weight of anisotropic petroleum bitumen.
5. The coating composition according to claim 1, wherein the secondary battery is a lead (Pb) battery, a nickel-cadmium (NiCd) battery, a nickel metal (Ni metal) hydride battery, a lithium-ion (Li-ion) battery, a solid-state battery, a soft carbon battery, a hard carbon battery, or a lithium-ion polymer (Li-ion polymer) battery.
6. The coating composition according to claim 1, wherein the electrode active material is a negative electrode active material.
7. The coating composition according to claim 6, wherein the negative electrode active material comprises silicon (Si).
8. A secondary battery electrode material, comprising: Silicon-containing electrode active materials; and A coating layer covering the surface of the electrode active material. The coating layer is formed by carbonizing the coating composition according to claim 1.
9. A secondary battery electrode material, comprising: Silicon-containing electrode active materials; and A coating layer covering the surface of the electrode active material. The coating layer is comprised of the secondary battery electrode material in an amount ranging from 2.1% to 10.0% by weight, based on the total weight percentage.
10. The secondary battery electrode material according to claim 9, wherein the coating layer comprises carbonized petroleum asphalt.
11. The secondary battery electrode material according to claim 10, wherein the petroleum asphalt comprises isotropic petroleum asphalt and anisotropic petroleum asphalt.
12. The secondary battery electrode material according to claim 10, wherein the carbonized petroleum asphalt is carbonized at a temperature of 600°C to 800°C for 30 to 120 minutes.
13. The secondary battery electrode material according to claim 8 or 9, wherein the electrode active material comprises a non-porous carbon support, and the non-porous carbon support comprises any one or more of hard carbon and soft carbon.
14. The secondary battery electrode material according to claim 8 or 9, wherein the electrode active material comprises a porous carbon support, and wherein the silicon is disposed on the surface and inside the pores of the porous carbon support.
15. The secondary battery electrode material according to claim 8 or 9, wherein, based on total weight%, the secondary battery electrode material comprises silicon in an amount from 30.0% to 80.0% by weight.